NAUNGAN DALAM PERSPEKTIF AL-QUR'AN : STUDI TAFSIR MAUDHU'I - marito hasibuan (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
This research is motivated by the diversity of meanings of shade (zhilȃl). The word shade (zhilȃl) has been understood as positive, such as shade, shadows, shade and so on. However, the author found shade (zhilȃl) which has negative meanings, as found in the word of God surah al-Wȃqi'ah verse 43 "and in the shade of black smoke". The main issues discussed in this research are what the auspices of the Qur'an and those who received auspices in the Koran. The objectives to be achieved in this study are: to explain the meaning of shade in the Qur'an and to explain the people who get the shade presented by the Qur'an. The research style that the author uses in this discussion is patterned library (Library Research) with the interpretation approach maudhu'i by making the Qur'an and the books of interpretation as the main source (primary) and the author also refers to the books of hadith and books books related to this discussion as an additional (secondary) source. Based on the results of the library research that the author did, it can be seen that the shade in the Qur'an uses words that describe good (positive) traits or characters such as shade, shade and others. But shade is also used for negative things, such as shade is used for expressions that get shade in hell. The people who get shelter in the form of favor (positive) are the Children of Israel, people who believe and do good deeds, ashhab al-Yamin (right group), Prophet Musa and those who get shade in the form of punishment (negative) are: people who deny the truth, people who are shirk, ashhab syimal (left) and residents of Aikah.